Pointing the Way Choreographer Hans van Manen - Percival, John (Dance Books Ltd., Alton,Hampshire (UK), 2008)
I haven't even mentioned van Manen's photography, which is of a level that could have provided an alternative career, and has in fact had exhibitions. PALABRAS CLAVE: Nederlands Dans Theater, NDT, Netherlands, homosexuality, Hans van Manen, Astor Piazzolla, Mutation.